Selective laser trabeculoplasty: current perspectives - Leahy KE (Dove Medical Press, 2015)
Kate E Leahy,1 Andrew JR White1–3 1Westmead Hospital, Westmead, NSW, Australia; 2Centre for Vision Research, Westmead Millennium Institute, University of Sydney, Sydney, NSW, Australia; 3Save Sight Institute, University of Sydney, Sydney, NSW, Australia Abstract: Selective laser trabeculoplasty (SLT) has been used in the treatment of glaucoma for just over a decade. Here, we review the current literature in terms of suggested mechanism, efficacy, method of treatment, predictors of success, adverse events, repeatability, and cost of SLT. The exact mechanism by which SLT lowers intraocular pressure (IOP) remains unknown although circumstantial evidence has come in many forms in relation to structural alteration; oxidative stress and inflammatory responses; tight junction integrity; proliferative responses; and microbubble formation. SLT is as effective as argon laser trabeculoplasty and medications in reducing IOP in glaucoma and ocular hypertension. The treatment is not uniformly effective in all eyes, and its IOP-lowering effect decreases over time. High pretreatment IOP is the strongest predictor of success; however, significant pressure reduction has also been shown in normal-tension glaucoma and in patients already taking multiple antiglaucoma drops. Mild, transient adverse effects are common. Transient IOP spikes usually resolve quickly with or without antiglaucoma treatment but may be problematic in pigmented angles. The limited available evidence suggests SLT is repeatable and cost-effective for the treatment of glaucoma and ocular hypertension. Keywords: glaucoma, SLT, ocular hypertension, intraocular pressure